2000
DOI: 10.1097/00006123-200006000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Upper and Lower Subtotal Maxillectomy Approaches to the Cranial Base: Microsurgical Anatomy

Abstract: The upper and lower subtotal maxillectomy approaches provide wide but differing access to large parts of the central and lateral cranial base depending on the site of the osteotomies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 22 publications
0
28
0
1
Order By: Relevance
“…After extensive lateral wall resection, Goldberg et al (2000) found an average of 5.9 mm reduction in exophthalmos, which offers a reduction of 0-0.5 mm in proptosis for each cubic millimeter of orbital volume expansion because of its location (Gonzalez et al, 2002). It has also been reported that removal of up to 25 mm of the lateral wall of the orbital rim yields only 2-2.9 cc of volume (Hitotsumatsu and Rhoton, 2000;Unal et al, 2003;Beden et al, 2007). Baldeschi et al (2005) stated that removal of the lateral wall reduces exophthalmos by 2.3 mm, with a 13% incidence of new-onset diplopia, which usually resolves spontaneously in 4-6 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After extensive lateral wall resection, Goldberg et al (2000) found an average of 5.9 mm reduction in exophthalmos, which offers a reduction of 0-0.5 mm in proptosis for each cubic millimeter of orbital volume expansion because of its location (Gonzalez et al, 2002). It has also been reported that removal of up to 25 mm of the lateral wall of the orbital rim yields only 2-2.9 cc of volume (Hitotsumatsu and Rhoton, 2000;Unal et al, 2003;Beden et al, 2007). Baldeschi et al (2005) stated that removal of the lateral wall reduces exophthalmos by 2.3 mm, with a 13% incidence of new-onset diplopia, which usually resolves spontaneously in 4-6 months.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, surgical complications are less when approaching the lateral orbital wall (Beden et al, 2007). Some authors have converted a deep lateral wall decompression with fat debulking as the firstline surgical treatment and have reduced the risk of postoperative strabismus (Harris et al, 1998;Hitotsumatsu and Rhoton, 2000;Gonzalez et al, 2002;Graham et al, 2003). After extensive lateral wall resection, Goldberg et al (2000) found an average of 5.9 mm reduction in exophthalmos, which offers a reduction of 0-0.5 mm in proptosis for each cubic millimeter of orbital volume expansion because of its location (Gonzalez et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The picture consisting of orbital pain plus oculosympathetic palsy (ptosis and miosis) had, in consequence, an important clinical localizing value before the development of modern imaging methods. Advances in micro n e u ro s u rg e ry and better understanding of the microanatomy of the cavernous sinus 4 , 5 , pet rous apex 6 , 7 , orbit 8 and infratemporal fossa 9 , associated with the introduction of modern staining techniques, re t rograde axonal mapping 1 0 , 1 1 a n d i m m u n o c y t o c h e m i s t ry 1 2 yielded more complete i n f o rmation about the skull base innervation and its relation with pathophysiologic events involved in the genesis of Raeder's neuralgia.…”
Section: Dr Daniel Monte Serrat Prevedello -Rua Alcides Munhoz 433 -mentioning
confidence: 99%
“…Contém o ramo V2, o gânglio esfenopalatino e a porção terminal da artéria maxilar [19][20][21][22][23][24] .…”
Section: Casounclassified